The Urgency of Anti-SLAPP Regulatory Renewal in Indonesian Environmental Law - Kamal, Ubaidillah; Masyhar, Ali; Fikri, Muhammad Adymas Hikal; Rajib, Rayi Kharisma; Idris, Siti Hafsyah (Pandecta Research Law Journal, 2024)
Indonesian Environmental Law has regulated Anti-Strategic Litigation Against Public Participation (Anti-SLAPP) which guarantees protection to everyone who fights for the right to a good and healthy environment, not to be criminally prosecuted or sued civilly, as stipulated in Article 66 of the UUPPLH. Hope is still far from reality, because data shows that many communities and/or environmental warriors are victims of SLAPPs as part of the backlash from those they report or oppose when they participate and defend people's right to a good and healthy environment. This article aims to discuss; (1) Problems of Anti-SLAPP Regulation and Application in Indonesia and (2) The Urgency of renewal Anti-SLAPP Regulations in Indonesian Environmental Law. The research method uses normative juridical methods. The results of the discussion showed that (1) the problems of regulating and implementing Anti-SLAPP include three elements, namely legal substance problems, legal structure problems and problems in legal culture: and (2) There are at least 7 reasons that cause the urgency of renewal of Anti-SLAPP Regulations in Indonesian environmental law to be able to realize the protection of society participation in environmental protection and management.